2014
DOI: 10.1088/1742-5468/2014/06/p06002
|View full text |Cite
|
Sign up to set email alerts
|

The adaptive nature of liquidity taking in limit order books

Abstract: Abstract. In financial markets, the order flow, defined as the process assuming value one for buy market orders and minus one for sell market orders, displays a very slowly decaying autocorrelation function. Since orders impact prices, reconciling the persistence of the order flow with market efficiency is a subtle issue. A possible solution is provided by asymmetric liquidity, which states that the impact of a buy or sell order is inversely related to the probability of its occurrence. We empirically find tha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 34 publications
(132 reference statements)
2
11
0
Order By: Relevance
“…However, once a market order enters the opposite side of the order book, the price returns to the best price on the opposite side, thus restoring market efficiency. This finding is consistent with the result in certain empirical studies, such as Taranto et al (2014), who find that the persistence of order flows reduces and price efficiency is restored when the same sign of order flows enters the order book and that the depth on the opposite side shrinks but the price impact is likely to decrease significantly.…”
Section: Simulation Results In An Order-splitting Economysupporting
confidence: 91%
See 1 more Smart Citation
“…However, once a market order enters the opposite side of the order book, the price returns to the best price on the opposite side, thus restoring market efficiency. This finding is consistent with the result in certain empirical studies, such as Taranto et al (2014), who find that the persistence of order flows reduces and price efficiency is restored when the same sign of order flows enters the order book and that the depth on the opposite side shrinks but the price impact is likely to decrease significantly.…”
Section: Simulation Results In An Order-splitting Economysupporting
confidence: 91%
“…24. The uncorrelated returns in the presence of persistent order flows are consistent with the result in previous empirical studies, such as Taranto et al (2014).…”
Section: Resultssupporting
confidence: 90%
“…In the right hand side of the equation, σ and V are, respectively, the volatility of the traded instrument and the total traded volume over the order execution time scale T , Y 0 a dimensionless constant of order unity, and δ is the impact exponent in the range [0.4, 0.7]. Theoretical models allowing one to understand the mechanisms underlying this strongly concave, nonintuitive impact function, have been put forward in [6,9,11,12] (on a related topic, see also [13]). Still, whereas the description of the contemporaneous impact of orders in terms of Eq.…”
Section: Introductionmentioning
confidence: 99%
“…The asymmetric liquidity mechanism has been verified empirically [9] and its microscopic origin has been explored and elucidated in [18]. In this last paper it has been shown that agents executing incrementally a large order by splitting it in a large number of trades adjust the size of these trades in order to minimize their impact on price.…”
Section: The Long Memory Of the Marketmentioning
confidence: 91%